2013
DOI: 10.4293/108680813x13794522667445
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Obstructing Small Bowel GIST Tumor

Abstract: A laparoscopic approach to gastrointestinal stromal tumors (GISTs) of the small bowel seems to be a safe method even in the face of emergent surgery when open oncologic principles of bowel and tumor handling are followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The pathologic diagnosis of small bowel GIST tumor was the same in both cases. Each tumor had a different method of obstruction, with one causing a volvulus and the other an intraluminal obstruction; however, both were successfully removed laparoscopically [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic diagnosis of small bowel GIST tumor was the same in both cases. Each tumor had a different method of obstruction, with one causing a volvulus and the other an intraluminal obstruction; however, both were successfully removed laparoscopically [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Morrison and Hodgdon, recorded two patients of GISTs presented with acute intestinal obstruction. 18 We reported ileo-ceacal intussusception in two patients (5.4%) with ileal GISTs. Pirşcoveanu et al, reported ileoceacal intussusception as a case report.…”
Section: Discussionmentioning
confidence: 76%
“…Morrison and Hodgdon described 2 patients with a GIST who underwent emergency laparoscopy due to small intestine obstruction. 12 In a 59-year-old man, the obstruction was caused by an 8 cm pedunculated tumor, which provoked a rotation of the bowel and its mesentery. In another case of a 24-year-old woman, the obstruction resulted from intussusception of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…During surgery, special care shall be taken to avoid damage to the capsule of the tumor. 12 In the adjuvant treatment of patients with intermediate and high clinical aggressiveness according to the NIH, tyrosine kinase inhibitors are used because of the high risk of recurrence. 13 Additionally, a spontaneous rupture of the tumor or rupture during resection increases the risk of peritoneal recurrence and is considered an unfavorable prognostic factor.…”
Section: Discussionmentioning
confidence: 99%